What motivates indonesian customers to transact with specific merchants? investigating preferences in the BRImo application using the UTAUT model - Putra, M. Rezky Dwi; Millanyani, Heppy (Goodwood Publishing, 2025)
Purpose: This study examines the key factors that motivate Indonesian customers to transact with specific merchants through the BRImo application. Despite having 35 million users, BRImo underperforms compared to m-BCA in transaction volume due to technical and usability issues. Methodology: Data were collected through online questionnaires distributed via social media to 400 respondents. The data were processed using Excel and analyzed using PLS-SEM to assess direct and indirect effects among UTAUT-related variables. Results: Only three of fourteen hypotheses were supported. Effort Expectancy significantly influences Behavioural Intention (T = 2.195; p = 0.028), Promotional Activities show the strongest effect (T = 213.548; p = 0.000), and Behavioural Intention significantly affects Use Behaviour (T = 9.698; p = 0.000). Traditional UTAUT predictors Performance Expectancy, Social Influence, and Perceived Enjoyment were not significant. Conclusion: BRImo adoption is driven primarily by ease of use and strong promotional activities. BRI should prioritize improving app performance and expanding promotional programs to increase user engagement and competitiveness. Limitations: The study uses self-reported online data and a sample limited to active social media users, which may limit generalizability. It also excludes contextual factors such as security, literacy, and cultural influences. Contributions: The study provides insight into mobile banking adoption in Indonesia, showing the limited relevance of traditional UTAUT variables and emphasizing the roles of usability and promotional strategies.